The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1051/gse:2003056
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of designs for fine-mapping of quantitative trait loci using combined linkage disequilibrium and linkage

Abstract: -In a simulation study, different designs were compared for efficiency of finemapping of QTL. The variance component method for fine-mapping of QTL was used to estimate QTL position and variance components. The design of many families with small size gave a higher mapping resolution than a design with few families of large size. However, the difference is small in half sib designs. The proportion of replicates with the QTL positioned within 3 cM of the true position is 0.71 in the best design, and 0.68 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
2
17
2
Order By: Relevance
“…The observed increase in the power of LDLA over LA concurs with the results of Lee and van der Werf (2004). They simulated a QTL explaining 25% of the phenotypic variance segregating in a population of 128 individuals, belonging to between 2 and 64 half-sib families (ie between 64 and 2 individuals per half-sib family).…”
Section: Discussionsupporting
confidence: 68%
“…The observed increase in the power of LDLA over LA concurs with the results of Lee and van der Werf (2004). They simulated a QTL explaining 25% of the phenotypic variance segregating in a population of 128 individuals, belonging to between 2 and 64 half-sib families (ie between 64 and 2 individuals per half-sib family).…”
Section: Discussionsupporting
confidence: 68%
“…Additional value of LD is therefore limited for the 10 cM map as was observed in this study. The result based on the 2 cm map showed that LD information is of added value confirming the results obtained by Lee and van der Werf [13]. The map distance used in that study was 1 cM between markers.…”
Section: Additional Value Of Ld Informationsupporting
confidence: 89%
“…In case the QTL-allele is rare more parents should be used to increase the chance of including segregating families. The results by Lee and van der Werf [13] based on full sib or half sib pedigrees also indicated that the number of families should be balanced with family size for the highest accuracy. Van der Beek et al [1] used a deterministic approach to estimate the power of different designs.…”
Section: Choice Of Experimental Design For Pig Qtl Studies and Accuramentioning
confidence: 95%
See 2 more Smart Citations